An expansion study of genotype-driven weekly irinotecan and capecitabine in combination with neoadjuvant radiotherapy for locally advanced rectal cancer with UGT1A1 *1*1 genotype. (May 2019) - Guan, Yun; Shen, Yunzhu; Xu, Ye; Li, Chao; Wang, Jingwen; Gu, Weilie; Lian, Peng; Huang, Dan; Cai, Sanjun; Zhang, Zhen; Zhu, Ji
Background: In our previous dose-escalation study, we uncovered the maximum tolerated dose (MTD) of weekly irinotecan was escalated to 80 mg/m 2 and 65 mg/m 2 for UDP glucuronosyltransferase family 1 member A1 (UGT1A1) *1*1 and *1*28 rectal cancer patients in neoadjuvant chemoradiotherapy (nCRT). This is an expansion study for *1*1 patients. Methods: Patients with clinical stage T3–4, N0–2 rectal cancer eligible for preoperative chemoradiotherapy were screened for the UGT1A1*28 genotype. A total of 52 patients with the *1*1 genotype were enrolled. Whole-pelvic intensity-modulated radiation therapy was given in 50 Gy/25 fractions. Concurrently, irinotecan of 80 mg/m 2 and capecitabine of 625 mg/m 2 twice daily from Monday to Friday were administered weekly. Primary endpoint was toxicities; secondary endpoints included pathological complete response (pCR), tumour-regression grading, treatment compliance, overall survival, local recurrence and disease-free survival. Results: All patients completed capecitabine-based radiotherapy as scheduled, and 42 (81%) patients completed more than three cycles of weekly irinotecan. Overall, grade 3/4 toxicities were observed in 20 cases, including 11 leucopenia, 10 neutropenia and 12 diarrhoea. Forty-three patients (83%) underwent a radical surgery, and 12 were evaluated as pCR. Another four patients accepted a watch-and-wait strategy because of clinical complete response (CCR). Conclusions: Our data demonstrated manageable toxicities and an encouraging CCR rate for UGT1A1 *1*1 genotype in an enhanced neoadjuvant therapy. A phase III trial is ongoing to evaluate the value of irinotecan in neoadjuvant therapy (CinClare) [ClinicalTrials.gov identifier: NCT02605265].